Disposition of Mathematical Critical Thinking of High School Students In Mathematical Problem Posing on Self Confidence - Arnindia Via Mawardi; Pradnyo Wijayanti; Atik Wintarti (Journal of Medives: Journal of Mathematics Education IKIP Veteran Semarang)
Disposition is part of critical thinking, therefore, this study finds out the mathematical critical thinking disposition of high school students with high self confidence and low self confidence in proposing mathematical problems. This research is a descriptive qualitative research. The research took place at SMA Negeri 7 Surabaya. The subjects were selected based on purposive sampling from the existing class X, so two were selected consisting of one high self- confidence subject and one low self-confidence subject The researcher himself as the main instrument and data collector. Data collection techniques with assignments, questionnaires and interviews. The results showed that students with high self-confidence when making assumptions in problem solving (accepting and challenging) can show mathematical critical thinking dispositions, namely truthseeking and systematicity. When evaluating arguments, the disposition of mathematical critical thinking seen is analicity, systematicity, confidence in reasoning. When drawing conclusions, the critical thinking disposition seen is systematicity. The results showed that students with low self- confidence when making assumptions in problem submission (challenging aspect) can show mathematical critical thinking disposition, namely truthseeking and systematicity. When evaluating arguments, the disposition of mathematical critical thinking that is seen is analicity, systematicity, and Marturity of judgment. When drawing conclusions, the critical thinking disposition seen is systematicity.